2011
DOI: 10.1159/000330884
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal MicroRNA Expression in Ts65Dn Hippocampus and Whole Blood: Contributions to Down Syndrome Phenotypes

Abstract: Down syndrome (DS; trisomy 21) is one of the most common genetic causes of intellectual disability, which is attributed to triplication of genes located on chromosome 21. Elevated levels of several microRNAs (miRNAs) located on chromosome 21 have been reported in human DS heart and brain tissues. The Ts65Dn mouse model is the most investigated DS model with a triplicated segment of mouse chromosome 16 harboring genes orthologous to those on human chromosome 21. Using ABI TaqMan miRNA arrays, we found a set of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 266 publications
2
26
0
Order By: Relevance
“…In the present study, the challenge was to map miRNAs to specific gene targets and the molecular networks they regulate. Studies have provided insights into miRNA-mediated gene regulation in Ts65Dn mice, and the potential contribution to impaired hippocampal synaptic plasticity and neurogenesis, and the hemopoietic abnormalities observed in DS (20,21). The present study found evidence for the functional importance of several previously unknown miRNAs in DS.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the challenge was to map miRNAs to specific gene targets and the molecular networks they regulate. Studies have provided insights into miRNA-mediated gene regulation in Ts65Dn mice, and the potential contribution to impaired hippocampal synaptic plasticity and neurogenesis, and the hemopoietic abnormalities observed in DS (20,21). The present study found evidence for the functional importance of several previously unknown miRNAs in DS.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, chromosome 21 codes for at least seven miRNAs: miR-99a, let-7c, miR-125b-2, miR-155 and miR-802, and miR-nov1 and miR-nov2 (45). Although the targets and pathways of chromosome 21 miRNAs have not been determined, it has been proposed that overexpression of these miRNAs may contribute to the observed DS phenotypes, including increased incidence of autoimmune diseases (46)(47)(48)(49). Of note, it has been recently reported that the regulation of pGE is under the control of miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that in DS, disomic Gabrb3 is modified by overexpressed trisomic microRNAs (miRNAs) or transcription factors located on Hsa21 [2,3,28,80-82]. The trisomic region of Mmu16 in Ts65Dn mice harbours two of the miRNAs located on Hsa21, mir-155 and mir-802, [2,80,81,83,84] and these are overexpressed in Ts65Dn hippocampus and prefrontal cortex [80]. However, they are not predicted to target human or mouse Gabrb3 mRNAs [85-87].…”
Section: Discussionmentioning
confidence: 99%